A new phosphorus fertilizer blend enhances grain legume yield and profitability in northern part of Ghana - Adjei-Nsiah, S.; Ulzen, J. (Elsevier, 2024)
Low concentrations of phosphorus limit grain legumes’ yield in the northern part of Ghana. Smallholder farmers could benefit from P-fertilizer blends to improve yield. This study evaluated the responses of soybean, cowpea and groundnut to P-fertilizer blends and their profitability in researcher-managed and farmer-managed trials in Northern, Upper West, and Upper East regions. The experiment was set up in a cross-factorial arranged in randomized complete block design with four replications. The treatments were two types of P-fertilizer blends (triple superphosphate and new yaraLegume applied at 30 kg P ha−1), a control and three varieties each of soybean (TGX 1835-10E, TGX 1789-8E and TGX 1834-5E), cowpea (Padituya, Wang-Kae and Kirkhouse), and groundnut (Samnut 23, Samnut 22 and Yenyawwaso). P-fertilizer blends increased grain yield of grain legumes in researcher-managed trials. In the researcher-managed trials, P-fertilizer blends doubled the nodulation of soybean varieties but did not influence the nodulation of cowpea and groundnut. P-fertilizer blends increased P-agronomic efficiency over control; however, the different P-fertilizer blends had similar P-use efficiencies. In farmer-managed trials, only the yield of groundnuts varied with the different P-fertilizer blends in the Upper West region, suggesting that P utilization may be location-specific for groundnuts. P-fertilizer blends increased the grain yield of soybean and cowpea varieties in the Northern and Upper West regions but not the Upper East region. The interaction between soybean and cowpea varieties and P-fertilizer blends was not significant. P-fertilizer blends recorded a higher value cost ratios (VCRs) that can offset uncertainties in price fluctuations. The high VCRs indicated that P-fertilizer blends were profitable and could be used to improve the livelihoods of smallholder grain legume farmers. The study demonstrated that grain legumes responded to P-fertilizer blends and are profitable. However, the non-responsive nature of the Upper East soils needs to be investigated to make P-fertilizer blends profitable in the region.